SliMANO: an expandable framework for the management and orchestration of end-to-end network slices - Meneses, Flavio (2019)
This paper proposes a slice management and orchestration framework for abstracting the instantiation of end-to-end network slices, which are composed by a chain of both physical and virtual network functions. In this line, the proposed SliMANO framework is a plug-in based system that requests network resources and coordinates the interaction among network orchestration entities for its instantiation and chaining in order to perform an end-to-end slice. These entities could range from management and orchestration (MANO), Software Defined Networking (SDN) controllers and Radio Access Network (RAN) controllers. A proof-of-concept prototype was implemented and experimentally evaluated, with results showcasing its feasibility. The results revealed a increase in the delay, associated with instantiation and deletion operations, when compared with the recently introduced network slicing feature (NetSlice) of the Open-source Management and Orchestration (OSM). Results showed that the delay is mostly associated to SliMANO being an entity external to the orchestrator itself, which comes as a trade-off for its added inter-operation capabilities. Moreover, SliMANO goes beyond the MANO domain and actually allows the interaction with SDN and RAN controllers.